The Farmer Participation and Income Structure in Swamp Land Optimization Activities in Barito Kuala District, South Kalimantan - Yuldian Noor; Cakti Indra Gunawan (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2024)
Optimization of agricultural swamp land can have a positive impact on the socio-economic empowerment of communities around the land. This research aimed to scrutinize the farmer participation and income structure in swamp land optimization activities in Barito Kuala District, South Kalimantan. This research was a descriptive study using investigative survey data collection methods. Investigative survey research generates data by interviewing respondents. This research was conducted from March to November 2022. This study covered 4 villages in Barito Kuala Regency, South Kalimantan Province which include Sungai Rasau Village, Cerbon District and Palingkau Village, Bakumpai District, Jelapat II Village, Mekarsari District, and Tamban Sari Baru Village, Tamban District. The conclusion of this study is that farmers' participation in swamp land optimization activities is good, this is evidenced by farmers' ownership of the optimized swamp land ranging from 0.5-1 hectare, with a land ownership rate above 70%. On the other hand, swamp land optimization makes farmers active in seeking their income from on-farm activities, this is evidenced by the level of farmers' income from on-farm activities above 70%. Moreover, it is important to maintain the optimization of the swamp land in ensuring the farmer participation and income structure.